Pulse Cultivation- A Venture for Food, Nutrition and Livelihood - Barik, Arun Kumar (International Journal of Bio-resource and Stress Management, 2021)
Pulses (food legumes) occupy an important place in Indian agriculture. It provides food, nutrition and Environmental security in bringing income and employment opportunity through various improved technological interventions. Being the largest producer and consumer of pulses, India has to import 3-4 mt of pulses every year to meet its domestic demand. There is an urgent need to increase both productivity and production of pulses to bridge the gap between demand and supply. India needs to provide 39 mt of pulses with the availability of 52 g capita-1 day-1 of 1.69 billion people in the projected year of 2050. An additional area of 3-5 mha has to be brought under pulses with a productivity of 1200 kg ha1 against the current productivity of 841 kg ha1. New research efforts should be attempted to achieve a breakthrough in productivity of pulses. Development of widely adaptable short duration varieties with biotic and abiotic stress resistance, participation of rural youths in producing good quality seeds and establishing village seed hubs, preparation of value added products by women farmers in SHGs, raising minimum support price (MSP) and ensuring procurement are the key factors towards achieving self sufficiency in pulse production. This will increase income, combat malnutrition and provide employment for better livelihood of the resource poor farmers.